2018
DOI: 10.1101/431221
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Superresolved microparticle traction force microscopy reveals subcellular force patterns in immune cell-target interactions

Abstract: Force exertion is an integral part of cellular behavior. Traction force microscopy (TFM) has been instrumental for studying such forces, providing both spatial and directional force measurements at subcellular resolution. However, the applications of classical TFM are restricted by the typical planar geometry. Here, we develop a particle-based force sensing strategy, specifically designed for studying ligand-dependent cellular interactions. We establish a straightforward batch approach for synthesizing high… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…These values are similar to mean traction stresses measured for adherent and motile cells as measured with flexible post 31 or traction force substrates 32 . Other studies have shown forces within the phagocytic cup include compressive forces 33 on the target near the cup edge consistent with an actomyosin contractile ring 18 . In our data, we did not find an obvious change in the direction or magnitude of the force as the cup approached and passed the midway of the target as would be expected if the contractile force at the edge dominated the net force on the target.…”
Section: Supplementary Video 1 and Supplementarymentioning
confidence: 92%
See 1 more Smart Citation
“…These values are similar to mean traction stresses measured for adherent and motile cells as measured with flexible post 31 or traction force substrates 32 . Other studies have shown forces within the phagocytic cup include compressive forces 33 on the target near the cup edge consistent with an actomyosin contractile ring 18 . In our data, we did not find an obvious change in the direction or magnitude of the force as the cup approached and passed the midway of the target as would be expected if the contractile force at the edge dominated the net force on the target.…”
Section: Supplementary Video 1 and Supplementarymentioning
confidence: 92%
“…Top coverslips (22 × 22 mm #1.5; Fisher, USA) were silanized with HMDS (hexamethyldisilane) for 30 min at 80 deg. PA gel solution was prepared with standard reagents, but with the addition of 1% polyacrylic acid v/v to provide carboxylic acid groups for linkage of ECM proteins 33 Quickly, 2 µL APS was added to 125 µL of gel solution, vortexed for 2 seconds, and 10 µL were placed on the center of each round, 40 mm coverslip. A 22 × 22 mm coverslip was then placed on top of the PA to spread it evenly, and a 3 g weight was placed in the center to compress it.…”
Section: Forces and Actin Cytoskeletal Dynamics During Phagocytosis mentioning
confidence: 99%
“…These values are similar to mean traction stresses measured for adherent and motile cells as measured with flexible post 31 or traction force substrates 32 . Other studies have shown forces within the phagocytic cup include compressive forces 33 on the target near the cup edge consistent with an actomyosin contractile ring 18 . In our data, we did not find an obvious change in the direction or magnitude of the force as the cup approached and passed the midway of the target as would be expected if the contractile force at the edge dominated the net force on the target.…”
Section: Forces During Phagocytosismentioning
confidence: 92%
“…Top coverslips (22 x 22 mm #1.5; Fisher, USA) were silanized with HMDS (hexamethyldisilane) for 30 min at 80 deg. PA gel solution was prepared with standard reagents, but with the addition of 1% polyacrylic acid v/v to provide carboxylic acid groups for linkage of ECM proteins 33 Quickly, 2 µL APS was added to 125 µL of gel solution, vortexed for 2 seconds, and 10 µL were placed on the center of each round, 40 mm coverslip. A 22 x 22 mm coverslip was then placed on top of the PA to spread it evenly, and a 3 g weight was placed in the center to compress it.…”
Section: Methodsmentioning
confidence: 99%
“…CTL killing is exerted on an individual cell basis since it requires the polarization of the centrosome, which controls lytic granules, toward the site of TCR triggering, underscoring the specifically directed nature of exerting apoptosis and preventing damage to healthy tissue [135]. Indeed, the dynamics of CTL force exertion in the IS was recently measured directly using a newly developed superresolved microparticle TFM [136]. IS has been found to be a site of intense force exertion at the nanonewton scale and there existed a positive correlation between the stiffness of the target cell surface and the degree of cytotoxic granule release by CTLs [133,134,137].…”
Section: Mechanotransduction In T Cell Effector Functionmentioning
confidence: 99%